A novel reporter of Fgf5 expression to monitor the "stemness" ground state in mouse embryonic stem cells - Honório, Inês Agapito, 1988- (2011)
Tese de mestrado. Biologia (Biologia Molecular e Genética). Universidade de Lisboa, Faculdade de Ciências, 2011